Trends in Hypertension Health Service Coverage in East Java Province, 2020–2022 - Praja Erwyanti; Regina Pindan; Nur Indah; Retno Ayu; Rahmawati (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Hypertension is a leading non-communicable disease affecting all age groups and is strongly associated with lifestyle, stress, and unhealthy diets. In East Java, hypertension service delivery has changed markedly, shaped by geography, facility availability, community awareness, and disruptions during the COVID-19 pandemic. Objective: To assess changes in hypertension-related health services in East Java Province from 2020–2022, focusing on sex differences and regional variation. Methods: A quantitative descriptive study using secondary data from the 2022 East Java Provincial Health Profile. Analyses summarized (1) trends in hypertension incidence and service utilization by sex during 2020–2022 and (2) changes in the provision of hypertension care across districts over the same period. Findings were presented as frequencies and trend comparisons. Results: Access to hypertension services increased from 2020 to 2022, suggesting post-pandemic recovery of service capacity and strengthened screening and early detection. In 2022, women accounted for the largest share of individuals receiving hypertension treatment, while the proportion of men treated increased compared with earlier years. This pattern may reflect improving health-seeking behavior among men and more accessible services. Conclusion: Hypertension service delivery in East Java improved over the last three years, accompanied by expanded access and early detection. Although women remain the majority of treated patients, male treatment uptake is rising. District disparities indicate the need for equitable planning to optimize hypertension management. Keywords: hypertension; health services; trends; East Java; sex differences